2014
DOI: 10.5751/es-06490-190252
|View full text |Cite
|
Sign up to set email alerts
|

Managing social–ecological systems under uncertainty: implementation in the real world

Abstract: ABSTRACT. Management decisions for natural resources are not made in a vacuum; the environmental and ecological conditions as well as the socioeconomic and political contexts affect goals, the choice of interventions, their feasibility, and which outcomes are obtained. Although uncertainty is recognized as a feature of natural resource management, little attention has been given to the uncertainty generated by institutional settings, historical contingency, and individual people's influence. These implementati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 68 publications
0
39
0
1
Order By: Relevance
“…For the latter two factors, dense and centralized networks with strong bonding ties are shown to be effective in managing simple tasks (Rico García-Amado et al 2012), while fragmented networks are shown to limit communication and hence adaptive capacity (Cárcamo et al 2014, Mannetti et al 2015. Furthermore, for successful transformation toward sustainable governance, studies indicate the need for decentralized and heterogeneous networks that entail bridging ties between administrative and institutional scales of management (Gelcich et al 2010, Cohen et al 2012, Marín et al 2012, 2015 and, in particular, the need for brokers who facilitate collaboration between these scales (Stein et al 2011, Cárcamo et al 2014, Moeliono et al 2014, Nuno et al 2014, Pietri et al 2015. Studies elaborating on possible reasons for inertia in governance processes reveal homogeneity among centrally positioned opinion-leaders as a potential barrier to collective action (Crona and Bodin 2006, Bodin and Crona 2008, Ramirez-Sanchez and Pinkerton 2009, Moeliono et al 2014, Mannetti et al 2015.…”
Section: Key Findingsmentioning
confidence: 99%
See 3 more Smart Citations
“…For the latter two factors, dense and centralized networks with strong bonding ties are shown to be effective in managing simple tasks (Rico García-Amado et al 2012), while fragmented networks are shown to limit communication and hence adaptive capacity (Cárcamo et al 2014, Mannetti et al 2015. Furthermore, for successful transformation toward sustainable governance, studies indicate the need for decentralized and heterogeneous networks that entail bridging ties between administrative and institutional scales of management (Gelcich et al 2010, Cohen et al 2012, Marín et al 2012, 2015 and, in particular, the need for brokers who facilitate collaboration between these scales (Stein et al 2011, Cárcamo et al 2014, Moeliono et al 2014, Nuno et al 2014, Pietri et al 2015. Studies elaborating on possible reasons for inertia in governance processes reveal homogeneity among centrally positioned opinion-leaders as a potential barrier to collective action (Crona and Bodin 2006, Bodin and Crona 2008, Ramirez-Sanchez and Pinkerton 2009, Moeliono et al 2014, Mannetti et al 2015.…”
Section: Key Findingsmentioning
confidence: 99%
“…The case studies deal with issues, ranging from climate policy (Moeliono et al 2014) to water and dryland management (Stein et al 2011, Sundstrom et al 2012, de Villiers et al 2014, Nuno et al 2014, Mannetti et al 2015 and coastal area management (Tompkins et al 2002, Crona and Bodin 2006, Bodin and Crona 2008, Ramirez-Sanchez and Pinkerton 2009, Gelcich et al 2010, Marín and Berkes 2010, Cohen et al 2012, Marín et al 2012, 2015, Cárcamo et al 2014, Pietri et al 2015.…”
Section: Strand (I): Natural Resource Governancementioning
confidence: 99%
See 2 more Smart Citations
“…The SES framework was developed as a diagnostic approach designed to aid the identification of common drivers of sustainability outcomes in natural resource systems (McGinnis and Ostrom, 2014;Ostrom, 2009); the PPD framework was developed to guide integrated social and ecological research (Collins et al, 2010); and the MSE framework is a simulation approach used in fisheries for testing management options under a range of uncertainties (André and Greg, 2007). The extension of some of these frameworks to conservation is currently being investigated Bunnefeld et al, 2011;Milner-Gulland et al, 2010;Nuno et al, 2014).…”
Section: Social and Ecological Systems Are Coupled And Interdependentmentioning
confidence: 99%